Standardizing Health Outcomes for Lung Cancer. Adaptation of the International Consortium for Health Outcomes Measurement Set to the Spanish Setting - Escudero-Vilaplana, Vicente; Calles, Antonio; Collado-Borrell, Roberto; Belén Marzal-Alfaro, María; Polanco, Carlos; Garrido, Carmen; Suarez, Jorge; Ortiz, Aurora; Appierto, Marilena; Comellas, Marta; Lizán, Luis (Frontiers in Oncology, 2020)
Purpose Lung cancer (LC) and its treatment impose a significant burden on patients’ life. However, patient-centered outcomes are rarely collected during patient follow-up. Filling this gap, the International Consortium for Health Outcomes Measurement (ICHOM) developed a standard set of variables for newly diagnosed LC patients. In order to facilitate the use of this standard set, the project aims to adapt it to the Spanish setting. Methods The variables (instrument and periodicity) to be included in Spanish standard set were selected through consensus during 4 nominal groups (13 oncologists, 14 hospital pharmacists, 4 hospital managers and 3 LC patients), under the supervision of a Scientific Committee (1 oncologist, 3 hospital pharmacists, 2 LC patients advocates). Results The variables agreed upon included: 1) case-mix: demographic [age, sex, education and social-family support], clinical [weight loss, smoking status, comorbidities (Charlson index), pulmonary function (FEV-1)], tumor [histology, clinical and pathological stage (TNM), EGFR, ALK, ROS-1, PD-L1] and treatment factors [intent and completion] and 2) outcomes: degree of health [performance status (ECOG) and quality-of-life (EQ-5D, LCSS)], survival [overall survival and cause of death], quality of death [place of death, end-of-life care and palliative care, death aligned with living will], treatment complications, and others [date of diagnosis and treatment initiation, productivity loss (sick leave)]. Conclusion The adaptation of ICHOM standard set to the Spanish setting pave the way to standardize the collection of variables in LC.